Age-dependent cognitive inflexibility in great apes. (April 2015) - Manrique, Héctor Marín; Call, Josep
Abstract : The ability to suppress and/or change behaviour on the basis of negative feedback, often conceptualized as cognitive flexibility, has rarely been investigated in nonhuman great apes across a broad age range. In this study, 25 chimpanzees, Pan troglodytes, eight bonobos, Pan paniscus, seven orang-utans, Pongo abelii, and three gorillas, Gorilla gorilla, whose ages ranged from 5 to 48 years, were presented with a transparent Plexiglas rectangular box horizontally attached to their cage mesh. A square container, 7.5 cm 2, fixed inside the apparatus contained a food reward (i.e. a grape). While the container rested on its central position the grape was not accessible. To retrieve the grape the subjects needed to grasp the handle connected to the reward container and displace it sideways to reach one of the lateral access windows. Subjects were intensively trained to displace the handle to a specific side (right or left, depending on the group) and then the rewarded side was reversed during the test. Performance in this reversal task did not differ significantly between species. However, a U-shaped relation between age and perseverative responding (i.e. moves to the previously rewarded side) was observed, extending findings with humans to our closest living primate relatives. Highlights: Apes' age influences performance on a simple reversal task. Cognitive flexibility of great apes proves to be age-sensitive. Effects of age on performance are similar within the apes' clade. The relationship between age and perseverative responding in great apes fits a U-shaped curve. Results with nonhuman great apes reproduce those reported in humans in equivalent tasks.